2020
DOI: 10.48550/arxiv.2005.08318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blind Direction-of-Arrival Estimation in Acoustic Vector-Sensor Arrays via Tensor Decomposition and Kullback-Leibler Divergence Covariance Fitting

Amir Weiss

Abstract: A blind Direction-of-Arrivals (DOAs) estimate of narrowband signals for Acoustic Vector-Sensor (AVS) arrays is proposed. Building upon the special structure of the signal measured by an AVS, we show that the covariance matrix of all the received signals from the array admits a natural lowrank 4-way tensor representation. Thus, rather than estimating the DOAs directly from the raw data, our estimate arises from the unique parametric Canonical Polyadic Decomposition (CPD) of the observations' Second-Order Statis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…Moreover, it can be easily shown that minimization of ( 9) is equivalent to maximization of the likelihood function for CN-distributed measurements (e.g., [22], Eq. ( 60)), which, in turn, is asymptotically equivalent to minimization of the optimally weighted nonlinear Least Squares (LS) objective function (see [22], Eq. ( 62), and Appendix E therein for the full details).…”
Section: Estimation By Kld Covariance Fittingmentioning
confidence: 99%
“…Moreover, it can be easily shown that minimization of ( 9) is equivalent to maximization of the likelihood function for CN-distributed measurements (e.g., [22], Eq. ( 60)), which, in turn, is asymptotically equivalent to minimization of the optimally weighted nonlinear Least Squares (LS) objective function (see [22], Eq. ( 62), and Appendix E therein for the full details).…”
Section: Estimation By Kld Covariance Fittingmentioning
confidence: 99%